The Utilization of Gracilaria sp. as Raw Material for Cellulose in Cellulose Acetate-Nickel Oxide (CA-NiO) as Electrode for Energy Storage Technology - Karim, Abdul; Ahmad, Ahyar; Arfah, Rugaiyah Andi; Ermawar, Riksfardini Annisa; Karim, Harningsih; Putra, Andi Erwin Eka; Putri, Suriati Eka; Negara, Satria Putra Jaya; Larekeng, Siti Halimah (Universitas Gadjah Mada, 2025)
In the modern era, electrical energy has become a significant need that drives the large consumption of fossil fuels and their environmental impacts. Supercapacitors can reduce this large consumption of natural polymers such as cellulose acetate (CA), which can be synthesized from Gracilaria sp. Composites with CA can be an environmentally friendly alternative electrode with low toxicity. The results show that the cellulose has been successfully synthesized from the algae Gracilaria sp., which was proven by FTIR spectra analysis. The results also show that supercapacitor electrodes have been successfully made where the manufactured electrodes form a composite between CA and nickel oxide (NiO), with the highest specific capacitance and specific energy values of 15.5 × 102 F/g and 13.3 × 102 Wh/kg, respectively, on the CA-NiO2 electrode, but when the NiO concentration is higher than the CA concentration the specific capacitance and specific energy decrease as shown on the CA-NiO electrode with NiO mass of 0.6 g. Thus, the materials results of this study can be applied to electric vehicles and technology that requires electricity storage in the future.